Characteristics in Maternal Case During COVID-19 in The Work Area of Patut Patuh Patju Hospital - Mega Sara Yulianti; Ni Komang Wijiani Yanti (Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2021)
The Covid-19 pandemic has caused disruptions in all sectors of life. The rapid spread of the virus causes morbidity and mortality rates to increase rapidly. Pregnant women are listed as one of the vulnerable groups at risk of being infected with Covid-19 because during pregnancy physiological changes occur which result in a partial decrease in immunity and can have serious consequences for pregnant women. The purpose of this study was to find out the characteristics of the mother in maternal cases during the Covid-19 pandemic at the Patut Patuh Patju Hospital in 2021. This research method uses a quantitative descriptive method with a retrospective approach in the Covid-19 Isolation Room at the Patut Patju Regional General Hospital, Lombok Regency. West from January 2021 to December 2021. The sample size in this study was 157 samples using total sampling. The analysis technique uses descriptive analysis. The results showed that the characteristics of mothers with the most productive age (20-35 years) were 96 (61.5%), the highest high school graduates were 73 (46.5%) and working mothers were 87 (55.1%) . The frequency of maternal cases during the Covid-19 pandemic with the most cases were KPD with 47 cases (29.9%), former SCs with 32 (20.4%) and incomplete abortion with 28 cases (17.8%).